Development of Tutorial Video For Higher Order Thinking Practice on the Topic of Newton’s Law - Nur Syaidah; Wayan Suana; Feriansyah Sesunan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
The aims of this research were to yield a product of question evaluation tutorial video higher order thinking of newton’s law which have been tested its validity, so that product developed effective used in study. Development models used in this research is the ADDIE model which consist of five stages: analysis, design, development, implementation, and evaluation. The result obtained from expert validation test with an average score of 3,53 with the qualifyng product is very valid, practitioners test result obtained an average score of 3,93 with very valid qualifyng, and one by one test results of the product was attractive, and easy to use. The result implementation of product showed if result learn the student reach the value KKM 75% than expected after using the developed product.